Hindu law beyond tradition and modernity - Menski, Werner (New Delhi ; Oxford : Oxford University Press, 2012)
This book analyses the development of Hindu law from the ancient period to its emergence as a postmodern phenomenon in the 21st century. The author uses comparative social theory literature to establish that Hindu law must be viewed both as an ancient, evolving conceptual entity and a living legal system.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hindus -- Legal status, laws, etc. -- India; Civil law -- India; Hindu law -- History